Work-family conflict and job satisfaction: the moderating effects of gender - Rahman, Mohammad Mizanur; Ali, Noor Azman; Mansor, Zuraina; Jantan, Amer Hamzah; Samuel, Adedeji Babatunji; Alam, Md. Kausar; Hosen, Sharif (Allied Business Academies, 2018)
The multi-group analysis based on the Structural Equation Modelling (SEM) was used to test the moderation effects of gender in the relationships between Work Family Conflict (W to FC) and Job Satisfaction (JS)/Family Work Conflict (F to WC) and Job Satisfaction (JS). Using convenience sampling technique, data was collected from 273 respondents who work as academicians in private universities in Bangladesh. The finding of this research is that gender doesn’t moderate the relationships between W to FC and JS/F to WC and JS. This study has added value to the Human Resource Management and Organizational Behaviour literature by determining the circumstances that influence both directions of W-FC on job satisfaction.